Ecogeographic land characterization map of the SADC region - Magos Brehm, Joana (2022)
With the aim of planning for the in situ and ex situ conservation of priority crop wild relatives (CWR) of the Southern African Development Community (SADC), a gap analysis at intra-specific level (i.e. ecogeographic diversity level used as a proxy of genetic diversity), was carried out. For this purpose, a generalist Ecogeographic Land Characterization (ELC) map for the SADC region was created using the ELC mapas tool of CAPFITOGEN (http://www.capfitogen.net/, Parra-Quijano et al., 2008, 2016) based on 16 ecogeographic variables from three different components (four geophysic variables, seven edaphic, and five bioclimatic; see the list below) at a resolution of 2.5 arc minutes (approximately 4.5 km at the equator). The Calinski-Harabasz (1974) criterion was applied to obtain an objective number of clusters for each bioclimatic, edaphic and geophysic multivariate analysis. The ELC map was then clipped to the SADC countries using ArcGIS 10.4.1 (ESRI, 2016). A total of 16 ecogeographic categories were identified in the SADC region with distinct ecogeographic characteristiscs (see file 'ELC_SADC_region_statistics.xlsx'). The files made available here include: the raster file of the ELC map of the SADC region (which is composed of 16 different files) and an Excel file which describes the statistics (i.e. average, median, maximum, minimum and standard deviation) of each ecogeographic category present in the map ('ELC_SADC_region_statistics.xlsx').